Use of Emerging Technologies and Non-Saccharomyces spp. for Tailoring the Composition of Yeast Derivatives: Effect on White Wine Aging - Sabrina Voce; Anna Bortolini; Lara Tat; Andrea Natolino; Piergiorgio Comuzzo (Foods, 2025)
Yeast derivatives are additives commonly used in winemaking for different purposes. Their manufacturing process is not well standardized, being mostly based on thermal inactivation and enzyme-induced lysis; furthermore, the main strain currently authorized for their production belongs to Saccharomyces spp. In this study, Saccharomyces cerevisiae and Torulaspora delbrueckii were used as starting microorganisms, whereas ultrasounds and high hydrostatic pressure were performed to induce autolysis, with the aim to evaluate the possibility to use different strains and emerging technologies as alternatives to the traditional methods to produce yeast derivatives. The chemical composition of the products obtained as well as the volatile profile of wines aged on yeast derivatives were mostly affected by the treatments performed during the manufacturing process. T. delbrueckii showed a good aptitude as starting microorganism for producing derivatives, whereas emerging, non-thermal technologies could replace the traditional methods for inducing autolysis, allowing to obtain products with enhanced content of polysaccharides (up to 178 mg/g) and antioxidant compounds (up to 9 µmol/g), and with low odor impact. The possibility to manage the chemical composition of yeast derivatives for specific winemaking purposes may thus be possible, by using specific starting microorganism and by applying the most suitable treatment to induce autolysis.